2003
DOI: 10.1289/ehp.6271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endosulfan on male reproductive development.

Abstract: There is experimental evidence of adverse effects of endosulfan on the male reproductive system, but there are no human data. Therefore, we undertook a study to examine the relationship between environmental endosulfan exposure and reproductive development in male children and adolescents. The study population was composed of 117 male schoolchildren (10-19 years of age) of a village situated at the foothills of cashew plantations, where endosulfan had been aerially sprayed for more than 20 years, and 90 compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
122
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(125 citation statements)
references
References 17 publications
0
122
1
2
Order By: Relevance
“…Dioxins and PCBs do not seem to affect pubertal development in girls, but one study reported an association of PCBs to a delay in pubertal development in boys (Den Hond et al, 2002). Endosulfan exposure was also associated with slower pubertal development in boys (Saiyed et al, 2003) and lead exposure with delayed pubertal timing in girls (Selevan et al, 2003;Wu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dioxins and PCBs do not seem to affect pubertal development in girls, but one study reported an association of PCBs to a delay in pubertal development in boys (Den Hond et al, 2002). Endosulfan exposure was also associated with slower pubertal development in boys (Saiyed et al, 2003) and lead exposure with delayed pubertal timing in girls (Selevan et al, 2003;Wu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Pubertal delay was associated to a high endosulfan exposure in a recent Indian study where 117 boys from a highly contaminated area were compared to 90 matched control boys from uncontaminated area (Saiyed et al, 2003). Antisteroidogenic properties of endosulfan could contribute to this effect.…”
Section: High Levels Of Pp'-dde Was Found In 26 Immigrant Girls Withmentioning
confidence: 99%
“…Interpretation of these findings may be limited by residual confounding and concerns about the analytical method of measuring the phthalate parent compound instead of the metabolites. 110 Saiyed et al 111 found that boys who were exposed to endosulfan in India were less mature and had lower testosterone and higher LH than unexposed boys.…”
Section: Human Studiesmentioning
confidence: 99%
“…In mice, endosulfan exposure resulted in increased testosterone metabolism and clearance (Wilson and LeBlanc, 1998). Studies involving children suggest that long term environmental exposure to endosulfan causes delayed male sexual maturation and reduced testosterone levels (Saiyed et al, 2003). The mechanism by which endosulfan may exert these effects may involve its ability to activate the human pregnane X receptor (PXR) and induce the expression levels of cytochrome P450 (CYP or P450) enzymes, thereby increasing metabolic rates.…”
Section: Introductionmentioning
confidence: 99%